VALIDITAS MIGRAINE SCREEN QUESTIONNAIRE MSQVERSI INDONESIA SEBAGAI ALAT PENAPIS MIGREN - Retno Jayantri Ketaren, Yusuf Wibisono, Henny Anggraini Sadeli (NEURONA, 2014)
INTRODUCTION MIGRAINE HEADACHE IS NOT ONLY SUFFERED BY THE ADULTS BUT ALSO BY CHILDREN THE PREVALENCE OF MIGRAINE IN SCHOOL AGES IS INCREASING EVERY YEAR THEREFORE A RELIABLE TOOL IS NEEDED TO DETECT MIGRAINE AS EARLY AS POSSIBLE MIGRAINE SCREEN QUESTIONNAIRE MSQ IS ONE OF THE MIGRAINE SCREENING TOOL THAT IS USED IN SEVERAL COUNTRIES